Disentangling the SDGs agenda in the GCC region: Priority targets and core areas for environmental action - Al-Saidi, Mohammad (Frontiers in Environmental Science, 2022)
The agenda of the Sustainable Development Goals (SDGs) is a key international outcome for guiding development efforts of nation states. However, SDG targets cover vast areas of action, and they are difficult to break down and monitor for countries with different developmental situations and needs. Often, global rankings of countries’ compliance with the SDG agenda are plagued with false signals and methodological limitations. This paper presents a much-needed prioritization of the SDG targets for the Gulf Cooperation Council (GCC) region. It maps SDG targets and outlines priorities and key areas for environmental action. Sustainability in resource use, consumption and production constitutes a primary area for investments. Education and awareness represent cross-cutting priorities and low-hanging fruit for action. Tackling climate change and emerging supply risks and the management of ecosystems represent an action area in which GCC governments can intensify their interventions. As a supporting policy, regional environmental cooperation is important for enhanced commitments and tackling transboundary aspects of the SDG agenda. The analysis of the SDG agenda in the GCC regions reiterates the importance of countries engaging with global sustainability framings in order work out their own interpretations in congruence with national development realities. Such an SDG regional mapping exercise also assists national-level planners or regional bodies working on development issues in shaping the Gulf region’s engagement with the global sustainability agenda and tracking progress on key SDG priorities.